THE PRACTICE OF ISLAMIC BUSINESS ETHICS IN SUSTAINING TRADITIONAL MSMES AMID DIGITAL TRANSFORMATION - Sabina, Aliyyah Azzah; Bahari, Raha (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2025)
In the digital era, most businesses leverage technology to increase their competitiveness. However, many traditional MSMEs in Pondok Ungu Permai, Bekasi City, still operate conventionally without the support of digital technology, yet they are still able to survive. This situation prompted this study to identify the role of Islamic business ethics in maintaining the sustainability of traditional MSMEs amidst the challenges of digitalization. This research is a socio-legal (empirical) legal research that examines law in social practices through collecting field data in the form of observations, interviews, and documentation of MSME actors in Pondok Ungu Permai, Bekasi. Data analysis was conducted inductively using a qualitative-descriptive approach. The results indicate that MSME sustainability is influenced by the application of Islamic business ethics, including the values ​​of monotheism, balance between profit and blessings, freedom of business, and responsibility. For example, business owners maintain honesty in pricing and weighing, are fair to customers, and prioritize trust in transactions. These findings confirm that MSME success is determined not only by the use of technology, but also by spiritual and moral values. Furthermore, the support of the Bekasi City Government strengthens MSME resilience through business development and facilitation, thus contributing to the local economy and community welfare.